PALLIATIVE CARE - Alexandru C. Grigorescu (Oncolog-Hematolog.ro)
Palliative care at the end of life, according to main medicine societies of the world Assessing the perception of the concepts of symptomatic and supportive treatment among medical personnel and medical students